The neurodevelopmental outcomes of neonatal intensive care unit survivors attending the neonatal follow up clinic at a central academic hospital in Gauteng - Rosie, Samantha Claire (My University, 2016)
Background: Neonatology has made astounding advances in intensive care which has improved outcomes and survival of infants with serious medical and surgical conditions (Browne 2011; Khan-D'Angelo et al. 2012; Purdy & Melwak 2012). The long term effects that the NICU environment, as well as varying neonatal morbidities, have on NICU graduates may be detrimental to neurodevelopment (Pineda et al. 2014; Leppert & Allen 2012). Developing countries such as South Africa readily adopt the afore-mentioned advances in neonatal care but fail to provide the adequate follow up that is needed for high risk infants (Ballot et al. 2012). Aim: To assess the neurodevelopmental outcomes of babies discharged from the Chris Hani Baragwanath Academic Hospital NICU when they attend the neonatal follow up clinic. Methods: 40 participants were assessed according to corrected age, using the Bayley Scales of Infant and Toddler Development Third edition. Results: Data from 20 male and 20 female participants were analysed. The mean corrected age at time of assessment was 147 days (±38). The mean cognitive score was 87 (Low average), mean language score was 96 (Average) and mean motor score was 93 (Average). It was found that participants with sepsis during NICU admission were at risk of abnormal cognitive development (P=0.018) at a 5% level of significance. On the language scale, no characteristics were significant at P=0.05. However PDA (P=0.076) and RDS (P=0.057) were found to be risk factors for abnormal language development at a 10% level of significance. Participants born via NVD (P=0.004) and those who experienced anaemia (P=0.038) during NICU admission were found to be at risk of abnormal motor development, at a 5% level of significance. Twenty one percent of participants had confirmed neurological fallout. Two participants were diagnosed with CP Conclusion: From the results of this study it is clear that infants who had fewer complications during NICU admission had higher neurodevelopmental scores on the Bayley-III. Infants who had many (or more than four) complications as well as a long duration of stay in NICU were more likely to have lower scores on the Bayley-III assessment. However, the mean Bayley-III scores of the population presented in this study (ranging from low average to average) would suggest that all infants who are discharged from an NICU are at risk for a degree of neurodevelopmental delay.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy Soweto, 2016